2016
DOI: 10.1016/j.jid.2016.07.015
|View full text |Cite
|
Sign up to set email alerts
|

5-Hydroxymethylcytosine Expression in Proliferative Nodules Arising within Congenital Nevi Allows Differentiation from Malignant Melanoma

Abstract: Differentiation of proliferative nodules in giant congenital nevi from melanoma arising within such nevi is an important diagnostic challenge. DNA methylation is a well-established epigenetic modification already observed in the earliest stages of carcinogenesis, which increases during melanoma progression. The ten-eleven translocation enzymes catalyze the oxidation of 5-methylcytosine to 5-hydroxymethylcytosine (5-hmC), which has recently been reported as an epigenetic hallmark associated with tumor aggressiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 69 publications
0
16
0
Order By: Relevance
“…Immunohistochemistry can be useful demonstrating immunohistochemical expression levels of Ki‐67 and PHHH3 in histologically benign and atypical proliferative nodules in CN . Recently, Pavlova et al emphasized the role of 5‐hydroxymethylcytosine (5‐hmC) in the differentiation of proliferative nodules from melanoma, as they demonstrated a high 5‐hmC expression (90.65%) in PN and a low or absent (7.8%) expression in melanomas.…”
Section: Lethal Versus Non‐lethal Paediatric Melanomasmentioning
confidence: 99%
“…Immunohistochemistry can be useful demonstrating immunohistochemical expression levels of Ki‐67 and PHHH3 in histologically benign and atypical proliferative nodules in CN . Recently, Pavlova et al emphasized the role of 5‐hydroxymethylcytosine (5‐hmC) in the differentiation of proliferative nodules from melanoma, as they demonstrated a high 5‐hmC expression (90.65%) in PN and a low or absent (7.8%) expression in melanomas.…”
Section: Lethal Versus Non‐lethal Paediatric Melanomasmentioning
confidence: 99%
“…46,47 Loss of 5-hmC has been shown to be a diagnostic hallmark of malignant melanoma and to distinguish among a spectrum of histologic and genetically distinct subtypes of melanoma and benign nevi with high sensitivity and specificity. [48][49][50][51][52][53] In general, benign melanocytic proliferations demonstrate strong nuclear reactivity for 5-hmC, whereas those with increasing malignant potential demonstrate increasing loss of 5-hmC, a finding that has been reproducibly observed in a number of independent studies. In the most recent and largest independent validation study to date, Saldanha et al 54 demonstrated that 5-hmC loss was, after controlling for existing staging and prognostic pathologic parameters, independently associated with worse prognosis and that the assay was easily and reproducibly performed.…”
Section: -Hydroxymethylcytosinementioning
confidence: 68%
“…54 A recent study also demonstrated its ability to consistently distinguish malignant melanomas from benign proliferative nodules arising within precursor giant congenital melanocytic nevi. 51 Unlike the assays discussed above that require macro/ microdissection of tumoral melanocytes, which are left vulnerable to inclusion of nuclei from benign precursor nevus cells, epidermal keratinocytes, or stromal/connective tissue cells, this immunohistochemistry-based assay for 5hydroxmethylcytosine enables evaluation at a molecular level of each individual cell of interest within the context of an entire histologic section (Figure 2, A through C). To this end, we have also demonstrated that this epigenetic biomarker may facilitate (1) microstaging and Breslow depth assessment of vertical growth phase melanomas associated with either small cell change, pseudomaturation, or preexisting nevus at the deepest aspect of the tumor 55 ; (2) risk assessment of heavily pigmented, histologically ambiguous, and malignant melanocytic tumors, including atypical deep penetrating nevi, pigmented epithelioid melanocyto- Figure 2.…”
Section: -Hydroxymethylcytosinementioning
confidence: 99%
“…Importantly, the expression of active TET2 or IDH2 into melanoma cells restores the 5-hmC landscape, inhibits melanoma proliferation, and increases survival in animal models [ 83 ]. The association between the loss of 5-hmC levels and malignant melanoma transformation was also supported through the study of proliferative nodules arising with congenital nevi; these nodules display some atypical features and predispose to malignant transformation, but were basically benign and exhibit—in contrast to melanomas—high 5-hmC levels and high TET2 and IDH2 activity [ 161 ]. TET2 and TET3 are silenced in melanoma cells by epigenetic mechanisms triggered by TGF-β and mediated by DNA methyltransferase 3A (DNMT3A); these events play a functional role in the epithelial-to-mesenchymal transition (EMT) and in metastatic processes of melanomas [ 162 ].…”
Section: Molecular Abnormalitiesmentioning
confidence: 99%